Elsevier-MTUN Symposium focuses on AI approach in improving the quality of teaching and learning - Naqiah, Puaad (UMPSA, 2024)
KUANTAN, 30 September 2024 - The organisation of the 3rd Elsevier MTUN Symposium in conjunction with Academia Day 2024 by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Elsevier focuses on artificial intelligence (AI) approaches in strengthening the quality of teaching and learning, especially in the Malaysian Technical University Network (MTUN).